Aprendizagem musical a partir da motivação: um estudo de caso com cinco alunos adultos de piano da cidade do Recife - Albuquerque, Artur Fabiano Araújo de (2011)
This research aimed to know the reasons why adults seek learning music through the piano. Sought to reflect on the relationship of teaching and learning the piano, the relevance of local social context, aspects of learning music on the piano by adults and some mental processes involved in the teaching of learning piano. The empirical field was the city of Recife, in 2010, bringing to the center of the investigation, five adults piano students. It was designed from the notorious great quest of adults in learning music through the piano. These adults were in a musical world understood within its context of action and construction. We designed a qualitative research, choosing the case study as a way to search multiple, semi-structured interviewing, and making our own interpretation through the data interface. This research was supported by studies addressing the issue of motivation, teaching music to adults and Music as social practice and sociocultural phenomenon. The sample showed a fairly high degree of amateurism, and the study of the piano often considered as a form of relaxation and stress relief. Shows that given the reality of what happens in the musical learning, there is a need for understanding on the part of music educators, and specifically the piano teachers, to conduct a study of contextualized teaching piano, without neglecting the clarity and obviousness of the parameters of musical language and technique on the piano. Teachers need to consider certain factors to plan their work, based on age, the peculiar aspects of motor development and the stated objectives. Recommendations are made for further studies on motivation and learning music at the piano to be performed within their contexts, which will expand the discussion so that music educators reflect on the teaching of piano teaching in its scope and relevance in the face of today.